Resenha: O populismo reacionário no Brasil: Projeto tradicionalista ou ambivalência da modernidade política? - Ribeiro, Marcos Abraão (Teoria & Pesquisa Revista de Ciência Política, 2024)
This review analyzes the book O Populismo Reacionario, which formulates a dialectic and plural interpretation of the internal and external factors that were decisive for the rise of the extreme right to the presidency of the Republic and its rooting in Brazilian political culture. The text combines, in a very well articulated way, political theory, constitutional theory, Brazilian legal and political thought, as well as institutional analysis that allow the formulation of an original theoretical contribution to understand the political tragedy of contemporary Brazil. The authors manage to convincingly support the novelty of reactionary populism in Brazil, by demarcating its globality as a political phenomenon and the particularities of its institutionalization in the country. However, I argue that Bolsonarism is an expression of the bipolarity of political modernity, and not an authentic reactionary movement that, from the point of view of political ideas and practices, aims to destroy political modernity.